STRATEGI PROMOSI DAN WORD OF MOUTH DALAM UPAYA PENINGKATAN KEPUTUSAN PEMBELIAN PRODUK TENUN - dewi astuti; Sri Ernawati (Distribusi - Journal of Management and Business, 2020)
This study aims to determine the effect of promotion strategies and WOM (word of mouth) on the purchasing decisions of woven products in Bima City. The type of research used is associative, research location in Bima City. The population in this study are all consumers who have bought a typical Bima woven fabric, the sample in this study amounted to 96 people with purposive sampling technique. The research instrument used a questionnaire with a Likert scale measurement. The type of data used in this study was quantitative data with research data sources, namely primary data. Data collection techniques are observation, questionnaire and literature study. Data analysis uses multiple linear regression. The results showed that the promotion strategy influences the purchase decision of woven products, WOM (word of mouth) influences the purchasing decision of woven products and WOM (word of mouth) more dominant influence the purchase decision of woven products in Bima City.